Concomitant herpes simplex virus colitis and hepatitis in a man with ulcerative colitis: Case report and review of the literature. Issue 42 (October 2016) - Phadke, Varun K.; Friedman-Moraco, Rachel J.; Quigley, Brian C.; Farris, Alton B.; Norvell, J. P.
Abstract: Background: Herpesvirus infections often complicate the clinical course of patients with inflammatory bowel disease; however, invasive disease due to herpes simplex virus is distinctly uncommon. Methods: We present a case of herpes simplex virus colitis and hepatitis, review all the previously published cases of herpes simplex virus colitis, and discuss common clinical features and outcomes. We also discuss the epidemiology, clinical manifestations, diagnosis, and management of herpes simplex virus infections, focusing specifically on patients with inflammatory bowel disease. Results: A 43-year-old man with ulcerative colitis, previously controlled with an oral 5-aminosalicylic agent, developed symptoms of a colitis flare that did not respond to treatment with systemic corticosteroid therapy. One week later he developed orolabial ulcers and progressive hepatic dysfunction, with markedly elevated transaminases and coagulopathy. He underwent emergent total colectomy when imaging suggested bowel micro-perforation. Pathology from both the colon and liver was consistent with herpes simplex virus infection, and a viral culture of his orolabial lesions and a serum polymerase chain reaction assay also identified herpes simplex virus. He was treated with systemic antiviral therapy and made a complete recovery. Conclusions: Disseminated herpes simplex virus infection with concomitant involvement of the colon and liver has been reported only 3 times in the published literature, and to our knowledge this is the first such case in a patient with inflammatory bowel disease. The risk of invasive herpes simplex virus infections increases with some, but not all immunomodulatory therapies. Optimal management of herpes simplex virus in patients with inflammatory bowel disease includes targeted prophylactic therapy for patients with evidence of latent infection, and timely initiation of antiviral therapy for those patients suspected to have invasive disease.